PEMANFAATAN SISTEM INFORMASI KEARSIPAN STATIS UNTUK MENUNJANG ARSIP POLITEKNIK NEGERI SAMARINDA - Halidin Noor (Jurnal Eksis, 2016)
Archival institutions tasked to manage an archive, that has a value to history, has exhausted its retention,and made permanent, For recorded information on all activies of organization, it serves as a centeral memory, decision making tools, evidence of the existence of organizationand for the benefit of another organization. Problems arise when the institution has a colltion of archival recorrds in abundance. A wide range of agency activities resulted generated archive colltion is very diverse. this causes the volume of records that are maintained very much.It difficult to find back of the shelf location manually,or with the list though,bacause the arschives are kept very much. In addtion to these problems, in general, have arcival decades old, making it susceptible to physical damage, In case of phycal touch to the archive continued in service activities and access, it is feared phyical harm will occuur archives. This study used a decriptive approach design,the research aim to collect an existing symptoms according to what the time of the study, and not to test the hypothesis. Data collection techigues used in this study is the observation, interviews,and documentation. Based on the results of this concluded that Politeknik Negeri Samarinda Archive used subject pattern in the management of the archive, The end of archive management is entering data into archive collection of archive information system. The information systim contains a database file thoroughly, so that the rediscovery of the archive manually. Keyword : Utlization, Information Systems, Archives